Literatura infantil en la estimulación del lenguaje oral en los niños de Inicial de la Unidad Educativa Liceo Policial. - Pallo Moya, Karina Alexandra (2024)
In the infant stage, children interact through language with their parents, classmates, teachers, and people close to them; through language, they express their needs, desires, and questions and facilitate the understanding of their environment. The main objective of this research is to analyze the interactions of children's literature as a sociocultural instrument with the stimulation of oral language in the children of Initial Education of the Liceo Policial Educational Unit. The referential framework of this project emphasizes the importance of communication from an early age and how language benefits or hinders infants from developing fully and safely in the educational environment. In addition, several factors that influence the development of language skills, such as migration, overprotection, and language problems due to alterations of the phono articulatory organs or delay, are evidenced. The methodology assumed a mixed approach, and the pre-experimental pretest-posttest design sought to analyze the certainty of the hypothesis proposed. Consequently, two instruments were used for data collection: an interview with the kindergarten teachers and a test adapted for 37 children. The hypothesis that children's literature as a didactic teaching resource stimulates the oral language of preschool children was accepted. In conclusion, children's literature as oral language stimulation allowed the children of the Liceo Policial Educational Unit to develop their linguistic skills; likewise, it expanded their vocabulary, creativity, and imagination by allowing them to develop their maximum expression.